Manajemen Pendidikan Multikultural-Religius Dalam Stratifikasi Sosial - Almaidah, Nirwana; Bakar, Abu (Institut Agama Islam (IAI) Faqih Asy'ari Kediri, 2023)
The term multicultural-religious education contains two integrated educational concepts, namely between multicultural education and religious education. Multicultural education is the basis of education that respects cultural pluralism, while religious education is the basis of education based on religious values ​​to give birth to religious people. The combination of these two educational concepts aims to be able to build an education system that can integrate both of them or reduce their weaknesses, especially to implement multicultural religious education management in the existing social stratification. With this there is a process of social change and heterogeneous or multicultural patterns of society. The main factors that determine a person's social strata are wealth, power, occupation, and education, but so are other factors, namely age, gender, religion, ethnic group, race, residence status, and other factors. Through multicultural education that has been managed with a management function, the attitudes and mindset of students will be more open to understanding and appreciating diversity.